Relações interorganizacionais de uma empresa que atua nos segmentos automotivo e de linha branca: análises de elos à montante e à jusante - Santos, Selma Regina Simões (Universidade Federal de São Carlos, 2012)
This survey aims to investigate the inter-organizational relationships of a company that in a same industrial plant, concentrates its activities into two distinct markets: the automotive and white goods. Therefore, its purpose is to identify and detail how different requirements of different economic sectors, characterized by unequal positions in supply chain and by physical flows and quirky information, interfere in the organizational design of a company that operates directly in two chains. To meet this goal, there was the selection of up-and downstream links, that is, suppliers and customers of the automotive and white goods market. Soon, was set a case study involving four suppliers and six central enterprise customers. The empirical clipping adopted contemplated the construction of immediate central chain company by which flow all interorganizational relations selected. The comparative research of upstream and downstream relationships occurred through questionnaires that sought to identify and translate the central company interactions with selected organizations, as well as to clarify their form of simultaneous actions in the sectors of automotive, white goods and with support of the theories of supply chain, supply chain management and networks. In summary, the results of this research showed that the company central: (1) Gets cost advantages in its operations in the automotive and white goods segment, on the basis of complementarities; (2) presents an organizational design shaped by the way in which production is performed to company C (b) 1, for the different sectors, by his training and entry into the market, by productive restructuring processes occurring in the white line and automotive markets, for its strategic options and by its placement in the automotive supply chain and white line; (3) when you join at the first level of the automotive supply chain had access to a large number of challenges and opportunities that, if properly addressed, will configure itself in a growth, characterized by structural changes that will include a new dimensioning of your strategic business units in order to remodel your current organizational design, as well as their relationships with customers and suppliers.
Keywords: Relações interorganizacionais; Indústria de linha branca; Indústria automobilística; Unidades estratégicas de negócios; Gestão da cadeia de suprimentos; Desenho organizacional; Inter-organizational relations; Organizational design; White goods; Automotive market; Strategic business units; Supply Chains; ENGENHARIAS::ENGENHARIA DE PRODUCAO